Surface Expression of GABA(A) Receptors Is Transcriptionally Controlled by the Interplay of cAMP-response Element-binding Protein and Its Binding Partner Inducible cAMP Early Repressor - Hu, Yinghui (American Society for Biochemistry and Molecular Biology, 2008)
The regulated expression of type A γ-aminobutyric acid (GABA) receptor (GABA(A)R) subunit genes plays a critical role in neuronal maturation and synaptogenesis. It is also associated with a variety of neurological diseases. Changes in GABA(A) receptor α1 subunit gene (GABRA1) expression have been reported in animal models of epilepsy, alcohol abuse, withdrawal, and stress. Understanding the genetic mechanism behind such changes in α subunit expression will lead to a better understanding of the role that signal transduction plays in control over GABA(A)R function and brings with it the promise of providing new therapeutic tools for the prevention or cure of a variety of neurological disorders. Here we show that activation of protein kinase C increases α1 subunit levels via phosphorylation of CREB (pCREB) that is bound to the GABRA1 promoter (GABRA1p). In contrast, activation of protein kinase A decreases levels of α1 even in the presence of pCREB. Decrease of α1 is dependent upon the inducible cAMP early repressor (ICER) as directly demonstrated by ICER-induced down-regulation of endogenous α1-containing GABA(A)Rs at the cell surface of cortical neurons. Taken together with the fact that there are less α1γ2-containing GABA(A)Rs in neurons after protein kinase A stimulation and that activation of endogenous dopamine receptors down-regulates α1 subunit mRNA levels subsequent to induction of ICER, our studies identify a transcriptional mechanism for regulating the cell surface expression of α1-containing GABA(A)Rs that is dependent upon the formation of CREB heterodimers.